Detection of capsulated Haemophilus influenzae in chest infections by counter current immunoelectrophoresis. Issue 1 (January 1978) - McIntyre, M
Abstract : The application of counter current immunoelectrophoresis to the detection of Haemophilus influenzae capsular antigen in sputum is described. The method, technically simple, provided results within 30 minutes. H. influenzae capsular antigen was detected in 12% of patients and in 54.8% of the H. influenzae strains isolated. The test was not impaired by prior antibiotic therapy.